Factors Associated With Working in Remote Indonesia: A National Cross-Sectional Study of Early-Career Doctors - Putri, Likke Prawidya; Russell, Deborah Jane; O'Sullivan, Belinda Gabrielle; Kippen, Rebecca (Frontiers in Medicine, 2021)
Background: Doctor shortages in remote areas of Indonesia are amongst challenges to provide equitable healthcare access. Understanding factors associated with doctors' work location is essential to overcome geographic maldistribution. Focused analyses of doctors' early-career years can provide evidence to strengthen home-grown remote workforce development. Method: This is a cross-sectional study of early-career (post-internship years 1–5) Indonesian doctors, involving an online self-administered survey on demographic characteristics, and; locations of upbringing, medical clerkship (placement during medical school), internship, and current work. Multivariate logistic regression was used to test factors associated with current work in remote districts. Results: Of 3,176 doctors actively working as clinicians, 8.9% were practicing in remote districts. Compared with their non-remote counterparts, doctors working in remote districts were more likely to be male (OR 1.5,CI 1.1–2.1) or unmarried (OR 1.9,CI 1.3–3.0), have spent more than half of their childhood in a remote district (OR 19.9,CI 12.3–32.3), have completed a remote clerkship (OR 2.2,CI 1.1–4.4) or internship (OR 2.0,CI 1.3–3.0), currently participate in rural incentive programs (OR 18.6,CI 12.8–26.8) or have previously participated in these (OR 2.0,CI 1.3–3.0), be a government employee (OR 3.2,CI 2.1–4.9), or have worked rurally or remotely post-internship but prior to current position (OR 1.9,CI 1.2–3.0). Conclusion: Our results indicate that building the Indonesian medical workforce in remote regions could be facilitated by investing in strategies to select medical students with a remote background, delivering more remote clerkships during the medical course, deploying more doctors in remote internships and providing financial incentives. Additional considerations include expanding government employment opportunities in rural areas to achieve a more equitable geographic distribution of doctors in Indonesia.